Promoting Deaf-Adults' Participation in Early Care and Education of Deaf Children. (19th November 2022) - Fobi, Daniel; Swanwick, Ruth; Asomaning, Derrick; Doku, Richard
Abstract: Few studies exist on the early care and education (ECE) of children who are deaf in low-to-middle-income countries, and none examine the roles of deaf adults in such provision. A research base is needed to inform contextually sensitive "deaf-infused" models of ECE in such contexts that build on indigenous deaf community experience, knowledge, and local expertise. This paper discusses the development of ECE in Ghana in sub-Saharan Africa focusing specifically on the perspectives of deaf adults on their roles in ECE support and leadership. Seventeen deaf adults with different leadership and advocacy roles in Ghana were interviewed about their perceptions of ECE priorities in this context, and the role of deaf adults in the development and delivery of early support. The participants expressed diverse views on ECE for the children and their families and suggested ways of building capacity and leadership among deaf adults to support ECE for the children and their families.